BNP/ NT-pro BNP thresholds for the assessment of the prognosis in patients without heart failure. (14th October 2021) - Hendricks, S; Mahabadi, A A; Vogel, L; Al-Rashid, F; Luedike, P; Totzeck, M; Rassaf, T; Dykun, I
Abstract: Background: Natriuretic peptides (BNP/NT-proBNP) are predominantly used for risk stratification, diagnosis and therapeutic monitoring in heart failure patients. A potential value of BNP/NT-proBNP serum levels for the prediction of prognosis in the general population and for non-heart failure patient cohorts is suggested in the literature. However, for non-heart failure patients, no thresholds are established. We aimed to determine cut-off levels that allow prediction of long-term survival in patients without known heart failure. Methods: The present analysis is based on a registry of patients undergoing coronary angiography between 2004 and 2019. Patients with existing diagnosis of heart failure or elevated natriuretic peptides (BNP >100pg/nl, NT-proBNP >400pg/nl), with missing follow-up information or without BNP/NT-proBNP levels at admission were excluded. As either BNP or NT-proBNP was available for singular patients and to adjust for the skewed distribution, BNP/NT-proBNP levels ranked based on gender specific percentile from 0 to 99. The cohort was then divided into a derivation and a validation cohort using random sampling. Incidence of death of any cause during follow-up was recorded. In the derivation cohort, cox regression analysis was used to determine the association of natriuretic peptides with incident mortality per 1 standard deviation increase in BNP/NT-proBNP rank. Multivariable models controlled for age, sex, LDL-cholesterol, systolic blood pressure, smoking status, and family history of premature cardiovascular disease. Receiver operating characteristics curve analysis was performed, with corresponding area under the curve, along with Youden's J index assessment, to establish a threshold for prediction of survival. The association of this threshold with incident mortality was tested in the validation cohort. Results: Overall, 3, 687 patients (age 62.9±12.5 years, 71% male) were included. During a mean follow-up of 2.6±3.4 years, 169 deaths occurred. In the derivation cohort, BNP/NT-proBNP was significantly associated with mortality (Hazard ratio [95% confidence interval]: 1.25 [1.01–1.54], p=0.04). Based on Youden's J index, BNP-thresholds of 9.6 and 29pg/ml and NT-proBNP thresholds of 65 and 77pg/ml for men and women, respectively, were determined. In the derivation cohort, BNP/NT-proBNP levels above these thresholds were significantly associated with increased mortality (2.44 [1.32–4.53], p=0.005). The predictive value of the determined thresholds was confirmed in the validation cohort (2.78 [1.26–6.14], p=0.01). Conclusion: We here describe gender-specific BNP/NT-proBNP thresholds that allow prediction of impaired survival in patients without heart failure. Utilization of these thresholds in clinical routine may qualify for risk prediction in non-heart failure cohorts, independent of traditional cardiovascular risk factors. Funding Acknowledgement: Type of funding sources: None.